Exploration of the Jumbo Basin iron deposit, Prince of Wales Island, southeastern Alaska - Wright, Wilford S.; Fosse, Earl L. ([Washington, D.C.] : U.S. Dept. of the Interior, Bureau of Mines, 1946)
"October 1946." Mode of access: Internet.